Assessment of Nuchal Translucency Nasal Bone and Ductus Venosus Flow in the First Trimester: Pregnancy Outcomes - Özdemirci, Şafak; Esinler, Deniz; Özdemirci, Funda; Bilge, Melek; Akpınar, Funda; Kahyaoğlu, İnci (Gynecology Obstetrics & Reproductive Medicine, 2014)
OBJECTIVE: To report the first trimester prenatal obstetric ultrasonography findings and pregnancy outcomes. STUDY DESIGN: This study was designed as a retrospective cohort one. Seven-hundreds twelve (n=712) singleton pregnant women attending to Simav –Kütahya Government Hospital between January 2008 and December 2011 for the routine first trimester screening and standard obstetric ultrasound examination were enrolled retrospectively. Pregnancy outcomes of these pregnancies were reported. RESULTS: The nasal bone was present in 704 (98.8%), absent in 4 (0.6%) and was not clearly evaluable in 4 (0.6%) patients. Blood flows in ductus venosus (DV) were normal in 609 (85.5%), reversed in 15 (2.1%) and not measurable in 88 (12.4%) of fetuses. We had 4 fetuses with cardiac anomaly. Among these 4 fetuses, we noted NT≥3.5 mm in 3 fetuses, absence of nasal bone in 3 fetuses and abnormal DV flow in 2 fetuses. We had 3 fetuses with Down syndrome. Among these 3 fetuses, we noted NT≥3.5 mm in 1 fetus, absence of nasal bone in 1 fetus and abnormal DV flow in 1 fetus. CONCLUSION: We reported our first trimester standard obstetric ultrasonographic results and pregnancy outcomes. We noted that the prenatal diagnosis of cardiac anomalies and Down syndrome may be possible via assessment of NT and DV flow.